Designing Video Storytelling Production for The Community of Kampung Gamis Karamat Mulya Village - Agung, Lingga; Al Ansory, Muchmammad Zaenal (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Kampung Gamis, located in Karamat Mulya Village, Soreang Subdistrict, Bandung Regency, Kampung Gamis, located in Karamat Mulya Village, Soreang Subdistrict, Bandung Regency, possesses a rich cultural and traditional heritage but faces challenges in preserving and promoting its cultural values in the digital era. This community service program aims to empower the Kampung Gamis community through storytelling technique training and video storytelling production. The activities are designed to enhance visual narrative skills, strengthen local identity, and leverage digital technology as a tool for cultural promotion and creative economic empowerment. The training follows a systematic approach that includes an introduction to the basic concepts of storytelling, video production techniques, practical editing using the CapCut application, and the implementation of storytelling techniques in video creation. Participants are encouraged to produce videos featuring narratives about local traditions and daily life, which are then presented and evaluated for improvement and appreciation. The outcomes of this program reveal an increase in participants’ technical skills in video shooting and editing, awareness of the importance of meaningful narratives, and the community’s ability to promote local culture through digital media. The expected impacts of this training include the strengthening of local cultural identity, enhanced community capacity as digital change agents, and the development of effective visual communication. By integrating technology and storytelling, this program not only preserves the cultural heritage of Kampung Gamis but also opens up opportunities for sustainable creative economic growth. This participatory, community-based approach serves as a strategic step in community empowerment and the development of village potential in the digital era.